2020
DOI: 10.3389/fphar.2020.602841
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Suspected Serious Adverse Drug Reactions in Corona Virus Disease-19 Patients Detected by a Pharmacovigilance Program by Laboratory Signals in a Tertiary Hospital in Spain: Cautionary Data

Abstract: BACKGROUND: From March to April 2020, Spain was the center of the SARS-CoV-2 pandemic, particularly Madrid with approximately 30% of the cases in Spain. The aim of this study is to report the suspected serious adverse drug reactions (SADRs) in COVID-19 patients vs. non-COVID-19 patients detected by the prospective pharmacovigilance program based on automatic laboratory signals (ALSs) in the hospital (PPLSH) during that period. We also compared the results with the suspected SADRs detected during the same perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
22
0
3
Order By: Relevance
“…Presence of comorbidities was also an independent risk factor (OR: 32.6; 95% CI 7.7-138; P < 0.0001). These ndings are consistent with the results of other studies which have shown polypharmacy and co-morbidity to be important risk factors for ADRs [4,8,9]. This association has been observed in non-COVID patients also [13,14].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Presence of comorbidities was also an independent risk factor (OR: 32.6; 95% CI 7.7-138; P < 0.0001). These ndings are consistent with the results of other studies which have shown polypharmacy and co-morbidity to be important risk factors for ADRs [4,8,9]. This association has been observed in non-COVID patients also [13,14].…”
Section: Resultssupporting
confidence: 93%
“…As a result, drug safety must be prioritized while maintaining e cacy. An increased incidence of ADRs has been reported in COVID patients as compared to non-COVID [4]. However, the prevalence of ADRs in critically ill COVID-19 patients is poorly understood, if precisely estimated, could help with the determination of the burden caused by multiple pharmacological therapies.…”
Section: Introductionmentioning
confidence: 99%
“…A multivariate analysis showed that the occurrence of ADRs has been associated with the length of stay (OR: 2.02, 95%CI: 1.03–3.96, P = 0.04), number of drugs used in hospital (OR: 3.12, 95%CI: 1.60–6.27, P = 0.001) and underlying diseases (OR: 2.07, 95%CI: 1.02–4.23, P = 0.045)[ 73 ]. In a prospective study using pharmacovigilance system in Spain, patients with COVID-19 had a higher incidence of hepatitis as a serious ADR than that in non-COVID-19 patients (45.1% vs 23.7%)[ 74 ]. In a meta-analysis of 10 studies, DILI in COVID-19 was reported in 25.4% of the total patients[ 5 ].…”
Section: Dili In Patients With Covid-19mentioning
confidence: 99%
“…In a meta-analysis of 10 studies, DILI in COVID-19 was reported in 25.4% of the total patients[ 5 ]. Therapies that have been implicated in hepatotoxicity included remdesivir, lopinavir/ritonavir, oseltamivir, hydroxychloroquine, paracetamol[ 5 ], tocilizumab[ 74 ], in addition to antibiotics, non-steroidal anti-inflammatory drugs, herbal medications, and interferon[ 34 ]. In a retrospective, observational cohort study ( n = 1827), the use of lopinavir/ritonavir, hydroxychloroquine, remdesivir, and tocilizumab was associated with statistically significant abnormal ALT and AST levels ( i.e.…”
Section: Dili In Patients With Covid-19mentioning
confidence: 99%
“…The variegatedness of symptoms exhibited makes it difficult to discern the true symptoms of COVID-19 from the offshoots or adverse drug reactions or after effects [15] . Such trials without proper appraisal of the efficacy of any of them singly or in combination has led to the deaths of millions of people the world over but the medical science fraternity is unrepentant as no responsibility can be fixed on either the healthcare professionals or the pharmaceutical companies or the allopathic healthcare system itself.…”
Section: Treatment Strategiesmentioning
confidence: 99%